Penerapan Prinsip Kehati-Hatian Direksi Pada Kegagalan Pengelolaan Investasi PT. ASABRI - Isnaini, Maulida; Sunarmi; Siregar, Mahmul; Lisa Andriati, Syarifah (LPPM Universitas Ekasakti Padang, 2024)
The law gives great authority to directors so that directors have freedom in running the company in order to achieve the company's goals and objectives. For this reason, when running a company, directors are required to always be careful in making decisions. The principle of prudence is part of the board of directors' fiduciary duty which must be implemented by every member of the board of directors. This research is aimed at analyzing the limits of prudence of insurance company directors in placing investments in company funds, as well as the legal consequences and responsibilities of company directors for violating the precautionary principle by making the case of PT. ASABRI as an object of study. This research is descriptive normative legal research with a statutory approach and a case approach. Data sources were obtained from primary and secondary legal materials collected using literature study techniques and analyzed using qualitative analysis methods. The results of this research found and concluded that legislation does not regulate in detail the limits of the prudential principle of directors in managing investments. However, directors are required to prepare an investment management plan that reflects investment policies and strategies, through a careful and accountable risk analysis and feasibility study process. In the case of the decision of the directors of PT. ASABRI which resulted in losses to PT. ASABRI, can be qualified as an unlawful act because it violates the precautionary principle, which is indicated by the actions of the directors who knew and approved the placement of PT investment funds. ASABRI in a number of companies without going through a risk analysis process and feasibility study. As a result of this violation of the precautionary principle, the directors of PT. ASABRI is personally and jointly responsible for the company's losses.